Organisational Baseline Study: Overview report for Pailom CSV, LAO PDR(LA02) - Villanueva, Jerome; Mienmany, Soytavanh; Souvannaxayyavong, Chantha; Phonevisay, Silivong; Xayachack, Anousith; Khodyhotha, Khamphamy (2015)
Savannakhet Province has a total area of 21,774 square kilometers, and in 2000 it had an estimated population of 757,950, with an average population density of 35 persons per square kilometer (DoP 2000). Agricultural production is the primary activity in the province and rice is the main crop being produce in the rural areas. Existing data suggest that Savannakhet Province has an estimated 116,809 hectares of rain-fed rice fields and approximately 19,801 hectares are irrigated rice fields. The number of livestock production has been recorded to be increasing and, at present, there are 79 pig farms, 19 poultry farms 15,924 man-made fish ponds, and 259 natural fish ponds (PAFO 2002). In terms of resources, Savannakhet is also rich in forest resources; in 2000 it still had 70 percent forest cover and included three national biodiversity conservation areas (NBCA), Phou Xang He (109,900 hectares), Dong Phou Vieng (197,000 hectares), and Xe Bang Noun (150,000 hectares). Economy wise, there are two state production forests in the province: Dong Ka Pho (9,600 hectares) and Dong Si Thounh (212,000 hectares) (MAF 2001 cited in Chanthavong, 2004). In partnership with IRRI, NAFRI and the District Agriculture and Forestry (DAFO), CCAFS has selected potential site for Climate-Smart Villages in Ban Phailom, Champone District. A 30km commute from Savannakhet town center on a poorly maintained road. Recent statistic suggests that Phailom Village has approximately 100 households. The population is mainly dominated by women about 430 and men are relatively smaller in proportion, only 269 individuals and 90% are involve in rice farming. At the village setting, rice paddy is estimated to be 222.59 hectares account for the majority of farmland landscape while only 7.82 hectares are considered irrigated land. The terrain in Phailom is classified into 2 terrain types, the Upper Phailom and Lower Phailom. Although the greater part of Ban Phailom is rain-fed rice farming, the lower area has reasonable access to irrigation but only confined to10 households. At a glance, it is evident that access to irrigation among rice farmers is a priority to enhance cropping system and overall farming productivity. As a whole, Savannakhet Province is thought to contain rich in natural resources and immense traditional agriculture production system (rain-fed rice production, aquaculture and small livestock raising) but pressure of change in weather pattern specially prolonged dry season will have a consequential impacts in the dynamics of farming communities undermining food security and livelihoods. The establishment of a CSV pilot site in Savannakhet particularly in Phailom Village is crucial to address the looming food insecurity brought about by changing weather patterns. Goal of Organizational Baseline Study are to: - Distinguish entry point for potential partnership and work synergy scheme with other organizations currently operating in the selected CCAFS CSV sites. - Provision of indicators that allows us to monitor changes in behaviors and practices of relevant local organization overtime. - Understand of the current status of provision of information/services at the local level that informs farmers’ decision making about their livelihood strategies in response to climate change. In order to collect the necessary information, the CSV team conducted a survey focusing on organization that was recorded during the second day of Village Baseline Survey with men and women discussion group. Information collected includes agriculture-related decision making, natural resources management, food security, food crisis, climate change perception and organization service activities.